OPTIMALISASI APLIKASI WHATSAPP DAN GOOGLE MEET UNTUK PENYAMPAIAN MATERI PADA PEMBELAJARAN JARAK JAUH - Dwi Ratih Yuliawati (PGSD Universitas Muria Kudus, 2021)
This study aims to analyze the use of the Whatsapp and Google Meet applications as an effort to optimize the delivery of material in distance learning at SMA N 1 Rembang.The research method used by researchers is descriptive qualitative research. Data collection techniques using interview techniques, observation, and documentation. The data obtained are in the form of interviews, observations and school documentation. Data analysis techniques using data verification techniques, data reduction and conclusions. To check the degree of truth using source triangulation.Teacher creativity is required to make students comfortable and enjoy the learning process without having to leave home and still follow the learning process. By combining several applications will complement each other so that it becomes the perfect learning. The use of the WhatsApp and Google Meet applications in one lesson will be complete in the distance learning process. Teachers can communicate easily using WhatsApp, can explain material clearly and can monitor students with Google Meet. In addition, teachers can provide attitude assessments automatically. The process of supervision in online learning using Whatsapp and Google Meet can also be done easily.